Autonomy as Dependence: Home-Based Education and Social Reproduction amongst Foreign Families in Bali - Molly Fitzpatrick (Faculty of Cultural Sciences, Universitas Gadjah Mada, 2025)
This paper explores the phenomenon of home-based education among foreign families living in Bali, Indonesia. Drawing on ethnographic research with sixteen families who participate in homeschooling, unschooling, and/or worldschooling, it examines the ways in which their political, educational, and parenting practices become intertwined in their everyday lives. While they imagine themselves to be preparing their children for a deterritorialised, globally mobile future, these families articulate a sense of detachment from what they call